1927 Haw. Sess. Laws 209-217, AN ACT Regulating the Sale, Transfer and Possession of Certain Firearms and Ammunitions, and Amending Sections 2136, 2137, 2138, 2139, 2140, 2141, 2142, 2143, 2146 and 2147 of the Revised Laws of Hawaii 1925 (the "Small Arms Act"), § 7, § 12, § 17 - (:unkn) unknown (General Publisher, 1927)
The judge of a court of record, or sheriff of the county, shall provide a license to carry upon the furnishing of proof of residence in Hawaii or the United States and good reason to fear injury to his person or property, or another good reason to carry. Prohibited providing false information or offer false evidence of identity. Violators punished by fine of not more than one thousand dollars or imprisonment for one year, or both fine and imprisonment.
--
Keywords: CARRY